Disponibilidade de alimentos saudáveis e não saudáveis em famílias com idosos e com longevos Pof 2017-2018 - Camargo, Liziane da Rosa (2021)
Introduction: Research surveys with data on household food availability, originating from the Family Budget Surveys (FBS) are of great value, as they enable the characterization of the diet of the Brazilian population in different family compositions, that is, with the presence of the elderly (60-79 years) and oldest-older (80 years or more). There is an absence of studies that seek to characterize the quality of the diet of the elderly and long-lived, which may be the precursor to the construction of a food security policy aimed at the older population. Objective: To compare the availability of healthy and unhealthy food items in families with and without the elderly and long-lived. Methods: It is an observational and cross-sectional study with secondary POF data, carried out by IBGE between 2017-2018. After exclusion criteria, 49,384 Brazilian families eligible for the research were identified, of these 13,805 with at least one elderly (28%) and 2,901 with at least one long-lived (6%). For the characterization of the family, the member with the highest age was considered, the families were divided into 3 groups, without elderly or long-lived (control), with elderly (elderly) and with long-lived (long-lived). Sociodemographic characteristics of the families and the food groups acquired by the families were obtained in the month surveyed. Results: The families were mostly composed of women. Families with elderly and oldest-older had lower average levels of education, higher total income (oldest-older), higher per capita income (elderly), greater predominance in white, even though the brown color was the most predominant in the total, more frequent in the urban household (oldest-older) and rural (elderly) and the most prevalent prevalent regions were the Northeast, Southeast and South. Sociodemographic characteristics influenced the availability of healthy and unhealthy foods in the surveyed families. Conclusion: With this study it was possible to compare the availability of healthy and unhealthy food items, according to the NOVA classification, in families with and without elderly and oldest-older. Families with the elderly and the oldest-older showed greater availability of healthy foods (fresh and minimally processed foods) and less acquisition of unhealthy foods (ultra-processed foods). The unfavorable nutritional transition process with the greater presence of ultra-processed foods seemed to be less evident in families with older age groups, which makes us believe that these families had healthier eating habits than young families (control).